Data-Based Planning Using Educational Reports in Improving Literacy - Mustari, Mohamad; Sudirman, Sudirman; Asrin, Asrin; Fahruddin, Fahruddin (Pascasarjana Universitas Mataram, 2024)
One of the efforts to improve the quality of education is planning according to the needs of the school. The education unit has an education report card in which there is information about quality indicators based on the National Assessment (AN) which is carried out every year where the results of the AN are described in the education report card which contains the report of the education unit as a whole starting from Numeracy Literacy, Instructional Leadership of school principals, educators and education personnel, and learning environment etc. Education units in Nusa Tenggara Province in general and in Mataram City in particular have implemented data-based planning (PBD), but it is not optimal because the program is relatively new. In the education report card, there are recommendations that are referred to as the preparation of the School Activity Plan and Budget (RKAS) in which there is a priority scale of recommended programs/activities such as improving teacher competence, increasing literacy and numeracy, strengthening character education and structuring the school environment. Through Community Service (PKM), in this case to junior high school education units, socialization programs/activities are needed through workshops with the theme of data-based planning.